Família e o trabalho profissional da/o assistente social no CRAS: entre a imediaticidade do cotidiano e a formação de sujeitos políticos - Guerra, Maria Natalia Ornelas Pontes Bueno (2017)
This thesis primary objective is to critically identify and analyze the professional work of social workers towards families in CRAS. The study based on social critique theory emphasizes traits preserved in socio-historical trajectory of Brazilian society which are determinants in the production of social inequality and poverty and the neoliberal hegemonic market model that structure the barbarism of today's society. It historically reconstructs the ways of being family to contemporaneity and the family that lives from work in this process, where their conditions of existence, their ways of thinking and acting are socially determined. In the field research, the qualitative methodology was used and it was possible to follow for three months the work developed by social workers in two CRAS, from different municipalities of the Metropolitan Region of Baixada Santista - RMBS. A semi-structured interview was also held for a dialogue with four social workers involved in these services. What is identified in the daily work carried out is a centralization in the family's immediate needs and emergencies, which produces an intervention focused on the unique lived, intrafamilial and social issues, without there being due problematization and contextualization of the social processes that produce these conditions.In this way the individual approach marks and dominates the professional work. Our thesis problematizes, defending the Family as a political subject that needs to be thought beyond the immediacy of everyday life, starting from the singularities, from the lived life, to the critical analysis of the relations present in the class society in the capitalist order of production. It challenges the professional work in the valorization of the population’s mobilization, organization and participation in defense of their rights in face of their necessities. It insists that we must produce collective experiences with effective emancipatory methodologies in building a democratic society in which human and social rights can be defended and made feasible